Multivalent Crown Ether Receptors Enable Allosteric Regulation of Anion Exchange in an Fe4L6 Tetrahedron. Issue 43 (27th September 2018) - von Krbek, Larissa K. S.; Roberts, Derrick A.; Pilgrim, Ben S.; Schalley, Christoph A.; Nitschke, Jonathan R.
Abstract: We report a strategy for regulating the rate of internally bound anion exchange within an Fe4 L6 metal–organic tetrahedron through external coordination of tripodal tris(alkylammonium) cations. The cage features three flexible 18‐crown‐6 receptors at each of its Fe II vertices, facilitating strong tritopic interactions with tris(ammonium) cations to "cap" the vertices of the tetrahedron. This capping mechanism restricts the flexibility of the cage framework, thereby reducing the rate of anion exchange within its central cavity by 20‐fold. Thus, we demonstrate the first use of an externally bound multivalent effector to allosterically control internal guest binding in a molecular cage. Abstract : Cagey about hospitality : Multivalent metal–organic cage receptors were prepared in a single step by subcomponent self‐assembly. A tetrahedral metal–organic cage was functionalized with four trivalent receptors. Trivalent effectors binding to the multivalent receptors in turn allosterically regulated the guest‐exchange behavior of the cage cavity.